Potential lifetime quality of life benefits of choroideremia gene therapy: projections from a clinically informed decision model - Halioua-Haubold, C-L; Jolly, JK; Smith, JA; Villanueva, R; Brindley, DA; MacLaren, RE (Springer Nature, 2019)
Background The first gene therapy for an inherited retinal dystrophy recently received market approval in the United States; multiple other gene therapies are in the clinical pipeline. Thus far, gene therapy has commanded prices in the range of USD 500,000 to over USD 1,000,000 for the one-time doses and have been indicated for highly orphan diseases where there is no other viable treatment option. To be adopted by healthcare systems, gene therapy will need to show clinical benefit in line with its increased costs. Before longitudinal patient studies are available, model-based estimations will be necessary to project the full clinical benefit of gene therapy. Methods To investigate the lifetime benefit of gene therapy for the retinal dystrophy choroideremia, we have built a Markov model of disease progression informed by clinical data of AAV.REP1 and voretigene neparvovec (Luxturna, Spark Therapeutics). Gene therapy patient benefit was estimated by quality-adjusted life years (QALYs) in three hypothetical disease severity patient groups. The severity of disease was defined by the combined effect of remaining retinal area and visual acuity and assigned corresponding health utility values. Results Early-stage patients treated with gene therapy were estimated to gain, in average, 14.30 QALYs over standard-of-care, mid-stage patients 6.22 QALYs, and late-stage patients 1.48 QALYs over untreated patients during their lifetime owing to treatment. Cost-effectiveness was not assessed as AAV.REP1 is still in clinical trials. Conclusions In young adults in the earlier stages of choroideremia, successful gene therapy is expected to provide a significant increase in health-related quality of life.